2018
DOI: 10.21037/jtd.2018.12.56
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of obstructive sleep apnoea and cardiovascular disease

Abstract: Obstructive sleep apnoea, the most common form of sleep-disordered breathing, is highly prevalent in patients with cardiovascular disease. The last 30 years has seen a plethora of large scale epidemiological studies investigating the relationship between sleep apnoea and cardiovascular outcomes. This review highlights the key epidemiological studies addressing the links between sleep apnoea and hypertension, cardiac arrhythmias, cerebrovascular disease, coronary artery disease, heart failure and pulmonary hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 92 publications
1
29
0
2
Order By: Relevance
“…Longitudinal community and sleep clinic cohort studies support an independent relationship between OSA and new CV events 6 including stroke 7 , myocardial infarction and heart failure 8 and CV mortality and the onset of CV risk factors such as hypertension 9,10 , diabetes 11 and atrial fibrillation (AF) 12 . Meta-analyses suggest that OSA is more strongly associated with cerebrovascular than coronary artery events 13,14 , and CV risk is greater in men than women.…”
Section: Cohort Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal community and sleep clinic cohort studies support an independent relationship between OSA and new CV events 6 including stroke 7 , myocardial infarction and heart failure 8 and CV mortality and the onset of CV risk factors such as hypertension 9,10 , diabetes 11 and atrial fibrillation (AF) 12 . Meta-analyses suggest that OSA is more strongly associated with cerebrovascular than coronary artery events 13,14 , and CV risk is greater in men than women.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…hypoxaemia, autonomic nervous system instability, mechanical loading of the heart and great vessels and sleep fragmentation. In light of the associations found in observational studies between OSA and CV disease and some CV risk markers6,14 , short-term randomised controlled studies of CPAP have been conducted to assess the effects of OSA treatment on key parameters of cardiovascu-…”
mentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is frequently seen in sleep-disordered breathing, which is found in 10% of people aged 30–70 years. OSA is characterized by repeated partial or complete obstruction of the upper airway that leads to arousal during sleep due to reduced airflow [ 1 3 ]. A large number of studies demonstrated that OSA is closely related to cardiovascular diseases (CVDs), such as hypertension [ 4 ], arrhythmia [ 5 ], heart failure (HF) [ 6 ], and coronary artery disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is the most common type of sleep‐disordered breathing. It is characterized by recurrent partial or complete obstruction of the upper airways during sleep, which leads to repetitive episodes of reduction (hypopnea) or absence of airflow (apnea) and intermittent hypoxia and arousal …”
mentioning
confidence: 99%
“…It is characterized by recurrent partial or complete obstruction of the upper airways during sleep, which leads to repetitive episodes of reduction (hypopnea) or absence of airflow (apnea) and intermittent hypoxia and arousal. 1 The major risk factors for OSA are obesity, male sex, and advanced age. 2 The prevalence of OSA is continuously increasing in developed countries in conjunction with the epidemic obesity.…”
mentioning
confidence: 99%